Experimental study and analysis of the dynamic mechanical properties of aluminium bronze - Li, Jinquan (Strojniški vestnik, 2015)
Accurate stress-strain curves of aluminium bronze (QAL9-4) under different temperatures and different strain rates were obtained using a dynamic compression test using a split Hopkinson pressure bar (SHPB). The dynamic mechanical properties of QAL9-4 were analysed. The Johnson-Cook (J-C) constitutive equation was obtained with experimental data fitting and the dynamic damage characteristics of QAL9-4 were studied using the mechanical response and microstructure analysis. The results show that QAL9-4 has an obvious strain-hardening effect and thermal softening effect, that the flow stress is not sensitive to the strain rate, and that the strain rate has almost no influence on the flow stress at room temperature and has a small effect at temperatures ranging from 300 °C to 700 °C. The fitting curves of the J-C constitutive model coincide well with the true stress-strain curves from the test.
Keywords: adiabatni strižni pas; aluminijev bron; deformacije; dinamične mehanske lastnosti; hitrost obremenjevanja; konstitutivna relacija